The Three Books on interes-bearing loans and interest (Foenus et Usurae) by Gerard Noodt, Jurist and Professor of Law - DM Kriel (Pretoria University Law Press (PULP), 2009)
The Three Books on interes-bearing loans and interest (Foenus et Usurae) by Gerard Noodt, Jurist and Professor of Law by SJ van Niekerk, JT Pretorius, DM Kriel and DH van Zyl 2009 ISBN: 978-0-9814124-0-5 Pages: 391 Print version: Available Electronic version: Free PDF available